Decreasing diameter fluctuation of polymer optical fiber with optimized drawing conditions. (2nd May 2018) - Çetinkaya, Onur; Wojcik, Grzegorz; Mergo, Pawel
Abstract: The diameter fluctuations of poly(methyl methacrylate) based polymer optical fibers, during drawing processes, have been comprehensively studied. In this study, several drawing parameters were selected for investigation; such as drawing tensions, preform diameters, preform feeding speeds, and argon flows. Varied drawing tensions were used to draw fibers, while other parameters were maintained at constant. At a later stage in the process, micro-structured polymer optical fibers were drawn under optimized drawing conditions. Fiber diameter deviations were reduced to 2.2%, when a 0.2 N drawing tension was employed during the drawing process. Higher drawing tensions led to higher diameter fluctuations. The Young's modulus of fibers drawn with different tensions was also measured. Our results showed that fiber elasticity increased as drawing tensions decreased. The inhomogeneity of fibers was also determined by comparing the deviation of Young's modulus.